An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar, 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China - Deng, Wei-An; Chen, Dan-Ni; Sheng, Qin; Zhao, Cong-Lin; Wu, Fei-Peng (Zootaxa, 2019)
The tetrigid genus Criotettix Bolívar, 1887 from China is taxonomically reviewed. The genus now includes 39 species from China, in which two new species are described and illustrated, namely: Criotettix longispinus Deng, sp. nov. and Criotettix undatifemurus Deng, sp. nov..Their distribution and an annotated identification key to Chinese species are provided.